Extraction of silicon carbide particles from rice husk / M. Kalaimani, Dr. T. Shaafi and Dr. A.Velumani - M., Kalaimani; T., Shaafi; A., Velumani (Faculty of Plantation and Agrotechnology, 2023)
Two techniques were employed to extract SiC from rice husk. First method is carbonization process of rice husks in a vacuum at temperatures between 300ºC - 700°C. Second method is carbonized rice husk was preformed carbothermal process in 90min at a temperature range of 1100ºC to 1600°C. SiC formations are occurred at 1600 °C and above. Yield of SiC formation as a function of the pyrolysis temperature of the carbonized rice husk.